2019
DOI: 10.3390/min9030139
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis for Assessing Sources, and Potential Risks of Polycyclic Aromatic Hydrocarbons in Lisbon Urban Soils

Abstract: Urban soils quality may be severely affected by polycyclic aromatic hydrocarbons (PAHs) contamination, as is the case of Lisbon (Portugal). However, to conduct a risk assessment analysis in an urban area can be a very difficult task due to the patchy nature and heterogeneity of these soils. Thus, the present study aims to provide an example on how to perform the first tier of a risk assessment plan in the case of urban soils using a simpler, cost effective, and reliable framework. Thus, a study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…In this study, the total concentration of the PAHs ranged from 0.36 to 11.49 mg/kg, with mean values of 1.99 mg/kg. Mean values indicated that soil were heavily contaminated against the permissible limits of 1 mg/kg [17] and polluted with pollutant of class III ranging from 1 to 5 mg/kg [19] Values are in line with the values which were found during research in Lisbon Urban Soils [18] and urban soils of southern Poland [10].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the total concentration of the PAHs ranged from 0.36 to 11.49 mg/kg, with mean values of 1.99 mg/kg. Mean values indicated that soil were heavily contaminated against the permissible limits of 1 mg/kg [17] and polluted with pollutant of class III ranging from 1 to 5 mg/kg [19] Values are in line with the values which were found during research in Lisbon Urban Soils [18] and urban soils of southern Poland [10].…”
Section: Discussionsupporting
confidence: 79%
“…g -1 . This indicates that oil areas have high levels of carcinogenic dangerous compounds that harm workers and humans in surrounding and Cachada et al (2019), and it was near to the study of Moore et al (2015).…”
Section: Table (4): the Percentage Of Pahs Compounds As Carcinogenic ...mentioning
confidence: 99%
“…These ubiquitous pollutants are distributed in environment and transport from soil to groundwater and plants causing human health risk (Cipa et al, 2018). PAHs compounds are very toxic and characterized for their potential influences of carcinogenicity, mutagenicity and teratogenicity, which are serious to human health due to their tendency to accumulate in the food chain (Cachada et al, 2019). Exposure to these compounds can cause many problems to human including irritation (eyes, skin, and mucous membranes), reduces the function bone marrow, weakness in nervous system and many types of cancers (Moore et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given that these compounds are carcinogenic, mutagenic, teratogenic and toxic to all living organisms, there is a need to monitor their concentration in soils [6,56]. PAHs are listed as priority pollutants by the European Union and the United States Environmental Protection Agency [14, 20,55], and they are becoming increasingly studied and tracked in soils worldwide [1,11,23,64].PAHs are often divided into 16 priority compounds. Among them, benzo[a]pyrene (BaP) is one of the most hazardous because of its carcinogenic and mutagenic properties and its persistence and bioaccumulation in the environment [66,78].…”
mentioning
confidence: 99%
“…Given that these compounds are carcinogenic, mutagenic, teratogenic and toxic to all living organisms, there is a need to monitor their concentration in soils [6,56]. PAHs are listed as priority pollutants by the European Union and the United States Environmental Protection Agency [14, 20,55], and they are becoming increasingly studied and tracked in soils worldwide [1,11,23,64].…”
mentioning
confidence: 99%